The Influence of Financial Stress on Student Consumption and Savings Behavior in the Era of Economic Crisis - Baharuddin, Andi Harnas; Ramlawati, Ramlawati; Suriyanti, Suriyanti (Maneggio, 2025)
This study aims to analyze the influence of financial stress on the consumption and savings behavior of college students during the economic crisis. The research method used a quantitative approach with a survey technique using a questionnaire to 200 college students as respondents. Data analysis was conducted through multiple linear regression tests to examine the relationship between variables. The results showed that financial stress had a positive and significant effect on college students' consumption behavior, while it had a negative and significant effect on savings behavior. These findings confirm that financial stress encourages increased consumption, both for primary needs and lifestyle, while simultaneously reducing students' ability to save. This study has important implications for college students, educational institutions, and policymakers regarding the need for financial literacy and personal financial management strategies amid the economic crisis.